Os efeitos da terapia por fotobiomodulaçao e da andiroba (Carapa guianensis) na lesão muscular induzida por contusão no músculo tibial anteror de rato - Ferreira, Tereza Cristina dos Reis (2018)
Physical activity, whether systematized and with professional or non-professional follow-up, is directly related to quality of life and disease prevention. However, accompanied by this growth, the number of muscular injuries was also increased. Muscle injuries can be caused by bruising, stretches or lacerations. More than 90% of all sports-related injuries are bruises or sprains. Foccusing on preventive care to reduce the risk of injury, exposure to photobiomodulation therapy (PBMT), pre- or post-activity, can protect vulnerable tissues to exercise-induced damage and speeding up recovery. It provides unique, non-invasive and non-pharmacological approach to reducing muscle fatigue. Andiroba (Carapa guianensis) is a medicinal plant traditionally used in the Brazilian Amazon region with known anti-inflammatory activity and extensive indication in skin diseases. Andiroba oil is rich in essential fatty acids, including linoleic acid wich has effect on lipid transport and metabolism in vivo, as well as for maintaining the function and integrity of cell membranes. The aim of this study was to analyze the effects of PBMT and andiroba oil on oxidative stress markers, histological analysis and proinflmmatory cytokine levels from rats after injury to the anterior tibialis muscle. Rats treated with PBMT plus andiroba oil (50% concentration) showed a reduction in lipid peroxidation 6 and 24 hours after muscle damage. Increased of glutathione peroxidase was observed in PBMT group, and increased superoxide dismutase in PBMT and PBMT plus andiroba oil 48 hours post-injury. The histological analysis showed discrete edema in the PBMT and PBMT plus andiroba oil groups. Necrosis was observed only in the group with tissue injury. A statistically significant reduction in IL-6 and TNF-α were observed 6, 24 e 48 hours after injury in the PBMT plus andiroba oil group. Our findings suggest a positive association of PBMT and andiroba oil in decrease the production of inflammatory mediators. However, further studies are necessary in order to conclude the positive assotiation between PBMT and andiroba oil. This fact may favor riparian communities that already uses andiroba oil on a daily basis injuries, as well as to provide to the scientific Community with new treatment options, since the anti-inflammatory effects of PBMT are not questionable, but its association with medicinal plants is still a new therapeutic aproach, with low costs and low side effects.